Effective Innovation for Competitive Advantage within a Manufacturing SME - Jackson, Alexander W M (2016)
This Management Project focuses on the topic of Effective innovation for competitive advantage within a manufacturing SME. Set against the practices of a specific study organisation, it has investigated methods by which the innovative practices in a manufacturing Small/Medium sized Enterprise can be audited and measured in order to ascertain their effectiveness. Having established the innovative practices that take place it identifies a list of recommendations and implications that aim to assist the organisation in evolving and improving innovative practices.